Paradigma Evaluasi Lembaga Pendidikan Islam: Mutu, Akuntabilitas, dan Nilai Islam - Saputra, Govi; Novianto, Chandra; Citra Dewi, Desy Eka (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The current evaluation paradigm in Islamic educational institutions tends to be administrative and summative in nature, resulting in limited impact on sustainable quality improvement. This study aims to analyze a holistic evaluation paradigm that integrates three main pillars: quality, accountability, and Islamic values. Using a library research method, this study examines the integration of Total Quality Management (TQM) with Islamic principles such as ishlah, itqan, ihsan, amanah, ‘adl, and hisbah. The findings reveal that the synergy of these three elements can transform evaluation into an educational, humanistic, and spiritually grounded process. This paradigm is expected to enhance transparency, public accountability, sustainable quality of Islamic education, and strengthen the formation of graduates with noble character amid the era of digital disruption.